An integrated urea and halogen bond donor based receptor for superior and selective sensing of phosphates. Issue 14 (12th March 2019) - Ghosh, Tamal Kanti; Mondal, Sahidul; Bej, Somnath; Nandi, Mandira; Ghosh, Pradyut
Abstract : An integrated urea and halogen bond donor based receptor is utilized for selective and superior sensing of phosphates. Abstract : A new Ru II based bis-heteroleptic ditopic receptor, 1[PF6 ]2 (C44 H33 F12 IN10 OP2 Ru), having integrated anion binding iodotriazole (halogen bond donor) and urea units (–NH bond donor) is employed for selective sensing of phosphates ( e.g., H2 PO4 − and HP2 O7 3− ).1[PF6 ]2 showed superiority in phosphate sensing in CH3 CN as compared to its hydrogen bond donor analogue, 2[PF6 ]2 (C44 H34 F12 N10 OP2 Ru), non-urea halogen bond analogue, 3[PF6 ]2 (C38 H27 F12 IN8 P2 Ru) and non-urea hydrogen bond donor analogue, 4[PF6 ]2 (C38 H28 F12 N8 P2 Ru) in terms of enhanced binding constant values, longer excited state lifetimes and lower detection limit values. 1 H-NMR, Isothermal Titration Calorimetry (ITC) and photophysical studies revealed the implementation of the combined role of both the halogen bond donor iodotriazole unit and the –NH unit of the urea moiety for selective and enhanced binding of phosphates.